2010
DOI: 10.1063/1.3437635
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching characteristics and mechanisms of Pt-embedded SrZrO3 memory devices

Abstract: Reproducible resistance switching characteristics of hafnium oxide-based nonvolatile memory devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] Up to now, most of the reported works about RRAM have mainly focused on demonstration of memory behaviors and switching mechanisms; few works have investigated the conduction behaviors and conduction mechanisms of the low resistant state (LRS) and high resistant state (HRS). [12][13][14][15][16] A good understanding of the current conduction in different resistance states would help to understand the physics behind the resistive switching phenomena, and it is also necessary to the RRAM applications. Current conduction and resistive switching in aluminum oxide films have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Up to now, most of the reported works about RRAM have mainly focused on demonstration of memory behaviors and switching mechanisms; few works have investigated the conduction behaviors and conduction mechanisms of the low resistant state (LRS) and high resistant state (HRS). [12][13][14][15][16] A good understanding of the current conduction in different resistance states would help to understand the physics behind the resistive switching phenomena, and it is also necessary to the RRAM applications. Current conduction and resistive switching in aluminum oxide films have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Among the insulators, TiO 2 is expected to have a high dielectric constant of 30-80 and offers a high V O formation controllability. In addition, Pt has shown potential as an electrode material because it can support V O formation and transfer into the TiO 2 layer during the setting and resetting of the resistive switching mode.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the basic structure of RRAM is the simple sandwich-like stack of a conductor/insulator/conductor, where the insulator is crucial to the characteristics of RRAM. Numerous semiconductor materials, such as perovskites [7][8][9][10] and binary metal oxides, [11][12][13] have been investigated as resistance switching (RS) materials for RRAM devices. However, the typical poor uniformity, large variations of switching parameters and high switching voltage limit the practical application of RRAM.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Doping, one of the mostly used techniques in semiconductor processing, has often been considered to modify the RRAM characteristics. 7,9,[14][15][16][17] Significant efforts have been made experimentally, for example, it has been demonstrated that Ga-doped HfO 2 14 and N-doped ZnO 16 have achieved significantly enhanced performance compared to their intrinsic semiconductor-based RRAM devices. However, technically, there are numerous potential dopants for RS materials and their effects on resistive switching are different and not clear.…”
Section: Introductionmentioning
confidence: 99%